Measurements of the normal size of spleen and spleen to left kidney ratio among sudanese children up to five years age using ultrasonography - Suliman, Awadia G.; Adam, Mohammed A.; Ahmed, Rihab Y.; Aburaida, Raga A.; Ebrahim, Ahmed A. (International Journal of Research in Medical Sciences, 2019)
Background: Knowledge of the normal range of spleen size in the population being examined is very important because there are many different pathological conditions that may alter in spleen size. Also, gender, height, weight and BMI of individual, affect the splenic length and could result in incorrect interpretation of splenic measurements, spleen to left kidney ratio is one of recent parameter mention in literature aid in diagnosis of splenomegaly in children. Methods: The study was a cross-sectional study conducted in Khartoum state at Al-Buluk and Gaafar Ibnauf Paediatric Tertiary Hospital during the period from March 2018 to August 2018. A total of 101 children (males and females) with aged ranged 1 month to 5 years included in study. A transabdominal scan was performed, and measurement of spleen and left kidney taken after an ethical verbal consent from their parents, then data analyzed by SPSS, Mean±SD. Deviation for study variables calculated then correlation between patients factors and ultrasound measurements done. Results: The study found that the mean measurements of the normal size of the spleen and spleen to left kidney ratio for children up to five years of age, Splenic length was 7.24±1.12 cm, width was 3.83±0.81 cm , thickness 2.91±0.55 cm and spleen to left kidney ratio was 1.04±0.0.70 ranged (0.86-1.23). The male have larger spleen than female with no statistically significant differences in spleen sizes between the sexes. There was a strong significant correlation between age, weight, height spleen and left kidney length (p<0.01)respectively and a moderate association with BMI (p<0.05). Conclusions: Spleen and left kidneys was growing rapidly and similarly in infant up to one year of life 1 mm\1 mm for each month and then decreasing growth rate of kidney in relate to spleen for 1 mm growth of spleen kidney grow 0.8 mm in up to five years of age. There was strong significant positive correlation between spleen and left kidney measurement with age, height, weight of individual. The spleen to left kidney ratio for children up to five years ranged (0.86-1.23) with mean 1.04, so if the ratio less or more than this ranged it should be considered in clinical context for diagnosis of splenomegaly or shrunken spleen in children up to five years of age.